Implementasi Komputasi Travel Time Seismik Refraksi Anisotropi dengan Metode Pseudo Bending - La Hamimu Hamimu (Program Studi Teknik Geofisika FITK UHO, 2023)
Numerical modelling of ray tracing from seismic refraction involving pseudo bending method and anisotropic attribute can be a new approach in understanding the wave propagation and calculating the travel time. The ray tracing of seismic refraction using the pseudo bending method provide a distinctive path for low and high velocity anomalous. The simulation result presented that travel time calculation for low velocity anomaly is greater than those of high velocity anomaly. Based on the type of media, ray tracing pattern and travel time calculations using the pseudo bending method also provided the different paths and travel time values for isotropic and anisotropic media. In an isotropic medium, ray tracing and travel time for direct shoot (DS) and reversed shoot (RS) configurations produced the same patterns and values. In contract, ray tracing patterns and travel time values in the DS and RS configurations demonstrated the different results for the anisotropic medium. Manifestly, these results provided significant confirmation of the fundamental concept that is the velocity of wave propagation in an isotropic medium does not depend on the direction of measurement, while in an anisotropic medium, the velocity of wave propagation was highly dependent on the direction of measurement